AMANAH DALAM PERSPEKTIF AL-QURAN (Studi Komparatif Tafsir Al-Misbah dan Al-Azhar) - Amiruddin Amiruddin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Amanah is one of the commendable qualities that must be possessed by a Muslim, where the nature of trust is the nature of carrying out all the responsibilities entrusted to someone in accordance with what is mandated without deviating in the slightest. The implementation of the mandate can provide welfare and justice to others. The purpose of this study is to compare to find the similarities of the two concepts of trust in the Koran an-Nisa verse 58 between the interpretations of al-Misbah and al-Azhar. This research method uses library research method. The primary data source in this study is the book of interpretations of al -Misbah and al-Azhar, secondary data sources are books or reading materials related to the interpretation of al-Misbah and al-Azhar in Surah an-Nisa verse 58. The results of the study formulate the conclusion that in the interpretation of al-Misbah amanah is that which has been handed over to those who are entitled to receive it, it should be carried out perfectly and on time, the same thing according to the interpretation of al - Azhar, the mandate should be handed over to experts according to their abilities and talents, the latter is more directed in terms of leadership. However, there are different interpretations of trust, according to al-Misbah's interpretation something that is handed over or entrusted to another party to be maintained and returned when the time comes to its owner, while trust according to al -Azhar's interpretation is something that is guarded to be conveyed to its owner.